“TUBIFEX INSTAN (FEXTAN)”: PAKAN ALTERNATIF BAGI UNIT PERBENIHAN IKAN LELE DI WILAYAH KABUPATEN NAGAN RAYA PROPINSI ACEH - Afrizal Hendri; Sufal Diansyah; Aris Yusdi; Sri Wahyuni; Mahyedin Salim; Burhanis Burhanis (Universitas Teuku Umar, 2022)
One of the critical phases in the production of lele sangkuriang (catfish) seeds is the rearing of larvae - post larvae - seed. During this phase, its growth is strongly influenced by feed, in particular natural feed and or feed that suits the needs of the fish. Tubifex sp type natural feed is one type of feed that is generally used by Balai Benih Ikan,BBI, fish state hatchery) during the rearing period of lele sangkuriang seed. The results of discussions and sharing with technicians and employees of BBI Parom Nagan Raya and surrounding fish farmers, information was obtained that so far they have been very dependent on live tubifex type natural feed ordered from North Sumatera Province for lele sangkuriang rearing (for fourteen days of rearing). The need for live tubifex for one cycle of activity is 5 kg-10 kg, at a price of Rp.100.000/kg (IDR), excluding the cost of box packing + shipping costs to Nagan Raya. Departing from the problem of these partners (BBI), the implementation team of the Pengabdian Berbasis Riset (PBR) of Universitas Teuku Umar (UTU), has agreed to introduce science and technology in the form of introduction of instant tubifex/fexTan artificial feed.